Towards a mining metaverse - Stothard, Phillip; Ryan, Peter; Kurata, Takeshi; Stapleton, Doug (Sage, 2024)
Access to persistent computer-generated virtual worlds may provide a powerful tool for conceptualising the mining cycle and managing the domains of exploration, feasibility, planning, design, construction, operations, rehabilitation, decommissioning and closure. Each domain presents a significant challenge to mine operations. Realisation of persistent virtual worlds that can be accessed by many simultaneously may be possible by leveraging Metaverse technologies to produce an ‘always on’ Mining Metaverse based on International Standards and industry collaboration. The realisation of a Mining Metaverse is a complex task because the Metaverse itself has many components and domains that must be managed effectively for it to be sustainable. This article introduces the complexity of the Metaverse components as a taxonomy and was inspired from collaborative work completed by the Standards Australia IT-031 Modelling and Simulation Committee and International Standards Organisation ISO/IEC JTC 1/SC 24 Committee. It is intended as a starting point for the mining industry towards understanding what the Mining Metaverse may be, and effectively embracing and managing this complex emerging technology in the future.